Large and expensive brain comes with a short lifespan: The relationship between brain size and longevity among fish taxa. Issue 1 (11th May 2022) - Stark, Gavin
Abstract: Vertebrates show substantial interspecific variation in brain size in relation to body mass. It has long been recognized that the evolution of large brains is associated with both costs and benefits, and it is their net benefit which should be favoured by natural selection. On one hand, the substantial energetic cost imposed by the maintenance of neural tissue is expected to compromise the energetic budget of organisms with large brains and their investment in other critical organs (expensive brain framework, EBF) or important physiological process, such as somatic maintenance and repair, thus accelerating ageing that shortens lifespan, as predicted by the disposable soma theory (DST). However, selection towards larger brain size can provide cognitive benefits ( e.g., high behavioural flexibility) that may mitigate extrinsic mortality pressures, and thus may indirectly select for slower ageing that prolongs lifespan, as predicted by the cognitive buffer hypothesis (CBH). The relationship between longevity and brain size has been investigated to date only among terrestrial vertebrates, although the same selective forces acting on those species may also affect vertebrates living in aquatic habitats, such as fish. Thus, whether this evolutionary trade‐off for brain size and longevity exists on a large scale among fish clades remains to be addressed. In this study, using a global dataset of 407 fish species, I undertook the first phylogenetic test of the brain size/longevity relationship in aquatic vertebrate species. The study revealed a negative relationship between brain size and longevity among cartilaginous fish confirming EBF and DST. However, no pattern emerged among bony fish species. Among sharks and rays, the high metabolic cost of producing neural tissue transcends the cognitive benefits of evolving a larger brain. Consequently, my findings suggest that the cost of maintaining brain tissue is relatively higher in ectothermic species than in endothermic ones.